2001
DOI: 10.1530/eje.0.1450785
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of insulin-stimulated GLUT4 translocation in skeletal muscle and adipose tissue in the Tsumura Suzuki obese diabetic mouse: a new genetic animal model of type 2 diabetes

Abstract: Background: In skeletal muscle and adipocytes, insulin-stimulated glucose transport has been known to occur through the translocation of glucose transporter (GLUT) 4 from the intracellular pool to the plasma membrane. The Tsumura Suzuki obese diabetic (TSOD) mouse, a new genetic animal model of type 2 diabetes, develops moderate degrees of obesity and diabetes that are especially apparent in animals more than 11 weeks old. A defect in insulin stimulation of GLUT4 translocation also contributes to the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…The TSOD mouse showed spontaneous obesity, glucosurea, hyperglycemia, and hyperinsulinemia only in male mice [25]. Miura et al reported that the insulin-stimulated translocation of glucose transporter (GLUT) 4 from low-density microsomal membranes to plasma membrane was reduced in both skeletal muscle and adipose tissue of TSOD mice, and that the reduced insulin sensitivity was presumably due to this impaired GLUT4 translocation in both skeletal muscles and adipocytes [15]. Using a whole genome scan of quantitative trait loci affecting body weight, blood glucose and insulin concentrations, Hirayama et al identified four major loci of the TSOD mouse meeting the rigorous criteria for linkage [11].…”
Section: Introductionmentioning
confidence: 99%
“…The TSOD mouse showed spontaneous obesity, glucosurea, hyperglycemia, and hyperinsulinemia only in male mice [25]. Miura et al reported that the insulin-stimulated translocation of glucose transporter (GLUT) 4 from low-density microsomal membranes to plasma membrane was reduced in both skeletal muscle and adipose tissue of TSOD mice, and that the reduced insulin sensitivity was presumably due to this impaired GLUT4 translocation in both skeletal muscles and adipocytes [15]. Using a whole genome scan of quantitative trait loci affecting body weight, blood glucose and insulin concentrations, Hirayama et al identified four major loci of the TSOD mouse meeting the rigorous criteria for linkage [11].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Tsumura Suzuki obese diabetes (TSOD) mice are novel polygenic models of spontaneous type-2 diabetes mellitus that develop moderate degrees of obesity, especially apparent in animals more than 11 weeks of age. 12,13 Unlike MSG mice, male TSOD mice showed glycosuria, hyperglycemia, and hyperinsulinemia without any special treatments. 14 In addition, the pathological characteristics of these mice were also examined under severe circumstances because steatohepatitis and liver nodules were frequently observed in male TSOD mice during preliminary examination.…”
mentioning
confidence: 99%
“…Furthermore, TSOD mice have several features similar to the pathologic condition and diabetic complications of human diabetes Type 2, including visceral fat accumulation, glucose tolerance, insulin tolerance, hypertension and peripheral neuropathy. 11,12,19) However, since TSOD mice had no deterioration of cardiac function except low R wave amplitude and myocardial damage in pathologic findings, despite their advanced age of 18 months, it seems that there was no onset of heart failure with diabetes (Figs. 2, 3, 4C).…”
Section: Discussionmentioning
confidence: 99%
“…10,11) Miura et al reported that the insulin-stimulated translocation of glucose transporter (GLUT) 4 from low-density microsomal membranes to the plasma membrane was significantly reduced in both skeletal muscle and adipose tissue of TSOD mice, and that reduced insulin sensitivity was presumably due to this impaired GLUT4 translocation in both skeletal muscles and adipocytes. 12) Hirayama et al identified three major loci meeting the rigorous criteria for linkage using a whole-genome scan of quantitative trait loci affecting body weight, blood glucose and insulin concentration. 13) However, no report has investigated the cardiovascular functions of TSOD mice.…”
mentioning
confidence: 99%